2012
DOI: 10.1051/kmae/2012016
|View full text |Cite
|
Sign up to set email alerts
|

Recapture and condition of pond-reared, and hatchery-reared 1 +  European grayling stocked in addition to wild conspecifics in a small river

Abstract: Key-words:Thymallus thymallus, river management, stocking, recapture, graylingThe relative performance of European grayling Thymallus thymallus reared in a hatchery on commercial dry feed or in a pond with natural food and their wild conspecifics, was assessed through recapture of tagged fish 5 months after their release into the Blanice River, Czech Republic. Oneyear old pond and hatchery reared fish from a resident broodstock were marked using Visible Implant Elastomer tags and released into 3 sections of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…The size of the fish, however, was smaller than in the hatchery (Ahlbeck and Holliland 2012). Pond rearing, as compared to tank rearing, had positive effects on recapture rates of European grayling Thymallus thymallus (Salmonidae) and brown trout stocked into natural rivers (N€ aslund 1992;Turek et al 2012). However, other studies on the same species have shown negligible or contrasting effects (Johnsen and Hesthagen 1990;Turek et al 2010).…”
Section: Pond Rearingmentioning
confidence: 98%
See 1 more Smart Citation
“…The size of the fish, however, was smaller than in the hatchery (Ahlbeck and Holliland 2012). Pond rearing, as compared to tank rearing, had positive effects on recapture rates of European grayling Thymallus thymallus (Salmonidae) and brown trout stocked into natural rivers (N€ aslund 1992;Turek et al 2012). However, other studies on the same species have shown negligible or contrasting effects (Johnsen and Hesthagen 1990;Turek et al 2010).…”
Section: Pond Rearingmentioning
confidence: 98%
“…Wild‐reared fish often perform better in the wild than pond‐reared fish (Miller ; Turek et al . ), suggesting that even if pond rearing increases the natural fitness of fish compared with tank‐rearing, it is still not alleviating all maladaptive effects of artificial rearing. There are also some other potential problems associated with pond rearing, like high temperatures, harvest inefficiency and distasteful flavour of the fish (Lawler et al .…”
Section: Treatments Closely Related To Structural Enrichmentmentioning
confidence: 99%
“…Stocking is routinely performed to limit the decline and to increase the population levels of fishes, despite the fact that it represents a significant risk for the conservation of indigenous, wild populations (Persat, 1996;Bohlin et al, 2002). Artificial rearing has been shown to substantially influence the behavioural traits of fishes, which may lead to reduced growth, survival rates and reproductive success of hatchery-reared fishes (Olla et al, 1998;Bohlin et al, 2002;Weir et al, 2004;Turek et al, 2012). For example, hatchery-reared fishes often display different foraging (Olla et al, 1998;Vehanen et al, 2009) or antipredator behaviours (Berejikian et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Between 8 and 9 months could be considered the most suitable age and length for turbot release, because they have an increased ability of swimming and finding shelter, whereas higher losses in hatchery-reared fish may be associated with predation (Turek et al 2012). The efficiency of turbot restocking programmes is often difficult to evaluate as information on natural stock abundance is rarely or only partially available.…”
Section: Capturementioning
confidence: 99%